Pengaruh Substitusi Limbah Cair Tahu Untuk Menstimulasi Pembentukan Lipida Pada Chlorella sp. - Harahap, Puspita Sari; Susanto, Antonius Budi; Susilaningsih, Dwi; Rahma, Delicia Yunita (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Chlorella sp. is one of microalgae which has potential lipid content. Chlorella sp. has a rapid growth rate and also easy to maintain. Therefore, chlorella has potency as source in biodiesel production.This aim of study is to determine substitution of carbon source as regular medium with tofu liquid waste to enhanced lipid production of Chlorella sp. This research was conducted by laboratory experimental method using Completely Randomized Design (CRD) with six treatments (three replicates) and one control. Material in this research is Chlorella sp. that obtained from Puslit Bioteknologi- Bioproses division, Lembaga Ilmu Pengetahuan Indonesia, Cibinong. Research’s data is analyzed using analysis variant (for the normal and homogenous data) or using non-parametric (for the abnormal and in homogenous data). The result of this study indicates treatment which has higher lipid is Chlorella sp.’s cultivation with tofu liquid waste addition 15 % in day 42nd (0,5160 g/ L), and treatment with tofu liquid waste addition 20 % in day 45th has the highest oil content (0,4040 g/ L).Culture of Chlorella sp. with tofu liquid waste as medium resulted decrese lipid production.